Energy and Environment Select Proceedings of ICWEES-2016 (Water Science and Technology Library,, 2018)
This book comprising seven parts is organized under two sections. The first section deals with environment containing four parts, whereas the second section, containing three parts, is on energy. The first part deals with some aspects of hydrologic impacts of global warming and anthropogenic changes. Part II is on bio-environment and discusses plants, biomass, and bacterial species. Part III focuses on chemical environment. Section one is concluded with Part IV on social environment. Section two starts out with Part V on solar energy. Hydropower is discussed in Part VI. The concluding Part VII deals with biogas. The book will be of interest to researchers and practitioners in the field of water resources, hydrology, environmental resources, agricultural engineering, watershed management, earth sciences, as well as those engaged in natural resources planning and management. Graduate students and those wishing to conduct further research in water and environment and their development and management may find the book to be of value.